2019
DOI: 10.1016/j.omtm.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of an AAV-Based MicroRNA Gene Therapy to Treat Machado-Joseph Disease

Abstract: Spinocerebellar ataxia type 3 (SCA3), or Machado-Joseph disease (MJD), is a progressive neurodegenerative disorder caused by a CAG expansion in the ATXN3 gene. The expanded CAG repeat is translated into a prolonged polyglutamine repeat in the ataxin-3 protein and accumulates within inclusions, acquiring toxic properties, which results in degeneration of the cerebellum and brain stem. In the current study, a nonallele-specific ATXN3 silencing approach was investigated using artificial microRNAs engineered to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 70 publications
0
37
0
2
Order By: Relevance
“…For SCA3, it was previously shown that targeting the expanded ataxin-3-allele by exon-skipping or ataxin-3 gene suppression using antisense oligonucleotides (ASO) in SCA3 mouse models result in lower polyQ-expanded ataxin-3 levels and in a reduction of aggregation [20][21][22]. Similar results are shown if the down-regulation of the disease protein ataxin-3 via specific micro-RNA (miRNA) is induced [23][24][25][26]. To get prepared for ataxin-3 lowering therapies in further clinical trials, our study aimed to establish sensitive methods to measure total full-length and polyQ-expanded ataxin-3 protein in PBMCs, an easily accessible human biomaterial.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For SCA3, it was previously shown that targeting the expanded ataxin-3-allele by exon-skipping or ataxin-3 gene suppression using antisense oligonucleotides (ASO) in SCA3 mouse models result in lower polyQ-expanded ataxin-3 levels and in a reduction of aggregation [20][21][22]. Similar results are shown if the down-regulation of the disease protein ataxin-3 via specific micro-RNA (miRNA) is induced [23][24][25][26]. To get prepared for ataxin-3 lowering therapies in further clinical trials, our study aimed to establish sensitive methods to measure total full-length and polyQ-expanded ataxin-3 protein in PBMCs, an easily accessible human biomaterial.…”
Section: Introductionmentioning
confidence: 74%
“…Therefore, measurements of ataxin-3 in PBMCs or—by more sensitive assays—in serum, plasma or CSF can pave the way for further clinical trials to track the disease progression and therapeutic response longitudinally. Our immunoassays are able to analyze ataxin-3 protein amounts under protein-lowering therapies like ASO or miRNA approaches as demonstrated by a miRNA approach using our SCA3 knock-in mouse model [ 26 ], thus representing promising pharmacodynamics/response biomarker which capture target-engagement in easily accessible peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…First studies have already used this KI model to prove antisense oligonucleotide (ASOs) therapy and longitudinal biomarker studies. Martier et al (2019) could recently show that they can reduce the amount of expanded Atxn3 mRNA in these KI mice by delivering microRNAs in an adenoassociated-vector system. Moreover, Wilke and colleagues are using this model to investigate the progression of neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH) as potential easily accessible serum biomarkers in a longitudinal study with mice in the age range from 2 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The highest CAG repeats were embryonically lethal while the shorter CAG repeats were tolerated ( Wang et al, 2011 ; Nalavade et al, 2013 ). Since the mutated ATXN3 gene produces a protein with a toxic gain of function, it is considered a promising target for gene silencing approaches such as ASOs and RNAi-based gene therapy ( Evers et al, 2014 ; Toonen et al, 2017 ; Martier et al, 2019c ).…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%